2018
DOI: 10.1515/jpm-2018-0066
|View full text |Cite
|
Sign up to set email alerts
|

Midwife-assisted planned home birth: an essential component of improving the safety of childbirth in Sub-Saharan Africa

Abstract: Hospital births, when compared to out-of-hospital births, have generally led to not only a significantly reduced maternal and perinatal mortality and morbidity but also an increase in certain interventions. A trend seems to be emerging, especially in the US where some women are requesting home births, which creates ethical challenges for obstetricians and the health care organizations and policy makers. In the developing world, a completely different reality exists. Home births constitute the majority of deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The second strategy involves interventions in the community targeted towards midwives and aimed at providing them with a higher education to complement their knowledge, and thus, enable them to seek care at institutionalized health centers [58] . Therefore, developing a model for midwife-assisted planned home births could be a relevant strategy to enhance the safety of home births [59] . The third is based on strategies involving the promotion of education, as well as the financing of higher education.…”
Section: Discussionmentioning
confidence: 99%
“…The second strategy involves interventions in the community targeted towards midwives and aimed at providing them with a higher education to complement their knowledge, and thus, enable them to seek care at institutionalized health centers [58] . Therefore, developing a model for midwife-assisted planned home births could be a relevant strategy to enhance the safety of home births [59] . The third is based on strategies involving the promotion of education, as well as the financing of higher education.…”
Section: Discussionmentioning
confidence: 99%
“…Among those who intended to deliver at a health facility but instead delivered at home, 45% indicated need for skilled delivery as a reason. While this seems counterintuitive, one reason for this may be the presence of traditional birth attendants (TBAs) in the community who women regard as skilled attendants 22 23. Although a policy change in Zambia resulted in TBAs no longer being trained and recommended that they stop conducting deliveries at home, a study on reasons for home delivery and use of TBAs in rural Zambia by Sialubanje et al found that most women had positive attitudes towards TBAs and regarded them as respectful, skilled and trustworthy 19.…”
Section: Discussionmentioning
confidence: 99%
“…Bob's last 15 years in research and academics were devoted to multiple scholarly endeavors, including writing commentaries and review articles, and espousing the need for increased responsibility and leadership among physicians in dispelling misinformation when counseling pregnant women about their chances of having a perfect baby, or about controversial topics such as planned home births and vaccinations (Brent, 2011; Chervenak et al, 2013; Chervenak, McCullough, & Brent, 2010, 2016; Dayyabu et al, 2018; Grünebaum et al, 2015; McCullough et al, 2016; McCullough, Chervenak, Brent, & Hippen, 2010).…”
Section: Researchmentioning
confidence: 99%